2015
DOI: 10.1111/nph.13401
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana HomeoBox 1 (AtHB1), a Homedomain‐Leucine Zipper I (HD‐Zip I) transcription factor, is regulated by PHYTOCHROME‐INTERACTING FACTOR 1 to promote hypocotyl elongation

Abstract: SummaryArabidopsis thaliana HomeoBox 1 (AtHB1) is a homeodomain-leucine zipper transcription factor described as a transcriptional activator with unknown function. Its role in A. thaliana development was investigated.AtHB1 expression was analyzed in transgenic plants bearing its promoter region fused to reporter genes. Knock-down mutant and overexpressor plant phenotypes were analyzed in different photoperiod regimes.AtHB1 was mainly expressed in hypocotyls and roots and up-regulated in seedlings grown under a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 64 publications
1
70
0
Order By: Relevance
“…Transgenic expression of Arabidopsis AtHB-1 in tobacco indicated a role in leaf development (Aoyama et al, 1995). Arabidopsis AtHB1 is regulated by phytochrome/PIF1 signaling and also plays a role in activating hypocotyl elongation (Capella et al, 2015). Therefore, downregulation of SbHB1 in phyB-1 buds is consistent with growth arrest and bud dormancy.…”
Section: Differential Expression Of Genes Encoding Transcription Factorsmentioning
confidence: 53%
See 1 more Smart Citation
“…Transgenic expression of Arabidopsis AtHB-1 in tobacco indicated a role in leaf development (Aoyama et al, 1995). Arabidopsis AtHB1 is regulated by phytochrome/PIF1 signaling and also plays a role in activating hypocotyl elongation (Capella et al, 2015). Therefore, downregulation of SbHB1 in phyB-1 buds is consistent with growth arrest and bud dormancy.…”
Section: Differential Expression Of Genes Encoding Transcription Factorsmentioning
confidence: 53%
“…AtHB1 regulates increased hypocotyl growth in response to light signaling through PIF1 (Capella et al, 2015). ENOD93 genes are involved in nodule development, and these genes are expressed in vascular bundles as well as the epidermis (Bi et al, 2009;Yan et al, 2015).…”
Section: Growth Arrest and Maintenance Of Cell Cycle Gene Expressionmentioning
confidence: 99%
“…Since different PIFs likely regulate the expression of at least partly shared target genes (Leivar and Monte, 2014), this would explain our observed partial overlap in the transcriptional response to shade and ethylene. PIFs also are known to directly bind and regulate the expression of other transcription factors like homeodomain transcription factors (Kunihiro et al, 2011;Capella et al, 2015) in the control of shade-avoidance responses. Indeed, our The Arabidopsis Information Resource motif analysis hinted at the presence of significantly enriched binding signatures of PIF/MYC proteins (CACATG) as well as homeodomain proteins (TAATTA) in the upstream promoter sequences of the Common Up set genes (Kazan and Manners, 2013;Pfeiffer et al, 2014;Supplemental Fig.…”
Section: The Convergence Of Signaling Pathways In Response To Ethylenmentioning
confidence: 99%
“…For KNAT5 and GTL1, previous studies showed high expression during the cell growth phase in the root and trichomes, respectively Breuer et al, 2009). For the other genes, expression profiling at a high cellular resolution is not reported so far, but the expression of HB1 and SHYG was shown to be increased during conditions inducing cell growth (Rauf et al, 2013;Capella et al, 2015). Furthermore, overexpression of HB1, SHYG, or ERF71 leads to increased cell size, while mutants for HB1 or SHYG are associated with reduced cell size (Rauf et al, 2013;Capella et al, 2015;Lee et al, 2015), indicating their roles in promoting cell growth.…”
Section: Identification Of a Novel Set Of Transcription Factors Involmentioning
confidence: 96%
“…These included AINTEGUMENTA-LIKE6 (AIL6; Mizukami and Fischer, 2000), CELL DIVISION CYCLE5 (CDC5; Lin et al, 2007), GROWTH-REGULATING FACTOR2 (GRF2; Gonzalez et al, 2010), ULTRAPETALA1 (ULT1; Carles et al, 2005), and MONOPTEROS (MP) and several of its targets, TARGET OF MONOPTEROS (TMOs; Schlereth et al, 2010). Roles of AIL6, CDC5, GRF2, ULT1, MP, and TMOs in the regulation of cell proliferation (Mizukami and In groups IV and V, showing an increase in transcription associated with cell growth, we identified factors with an expected potential to play roles in cell growth regulation, such as HOMEOBOX-1 (HB1; Capella et al, 2015), ETHYLENE RESPONSE FACTOR71 (ERF71; Lee et al, 2015), KNOTTED1-LIKE HOMEOBOX GENE 5 (KNAT5; Truernit and Haseloff, 2007), MINI ZINC FINGER1 (MIF1; Hu and Ma, 2006), SPEEDY HYPO-NASTIC GROWTH (SHYG; Rauf et al, 2013), OVATE FAMILY PROTEIN13 (OFP13; Wang et al, 2016), GT-2-LIKE1 (GTL1; Breuer et al, 2009), and HOMEODOMAIN-16 (HB16; Wang et al, 2003). For KNAT5 and GTL1, previous studies showed high expression during the cell growth phase in the root and trichomes, respectively Breuer et al, 2009).…”
Section: Identification Of a Novel Set Of Transcription Factors Involmentioning
confidence: 99%